Heterologous expression and characterization of a xylanase and xylosidase from white rot fungi and their application in synergistic hydrolysis of lignocellulose. (December 2018) - Zhuo, Rui; Yu, Hongbo; Qin, Xing; Ni, Haoxiang; Jiang, Zhen; Ma, Fuying; Zhang, Xiaoyu
Abstract: Endo-xylanase and β-xylosidase are the major enzymes for hemicellulose hydrolysis, which play a significant role in biomass conversion. In our previous work, the white-rot fungi Pleurotus ostreatus HAUCC 162 and Irpex lacteus CD2 were demonstrated to have strong ability in lignocellulose degradation, and the related lignin degradation enzymes were characterized. However, little was known about their hemicellulases. In this work, a novel endo-1, 4-xylanase and a β-xylosidase from Pleurotus ostreatus HAUCC 162 and Irpex lacteus CD2 were heterologously expressed and characterized. The optima of pH and temperature were 5.0 and 55 °C for rXyn162, and 6.5 and 30 °C for rXylCD2. rXyn162 showed high tolerance to metal ions such as Ca 2+, Cr 3+, Zn 2+, Na +, and Al 3+ . The recombinant rXyn162 and rXylCD2 exhibited synergistic hydrolysis of oat spelts xylan and sodium hydroxide pretreated cornstalk (SHPC), where the degree of synergy (DS) was 2.26 for SHPC hydrolysis. MALDI-TOF-MS and HPLC analysis showed that xylooligosaccharides (XOS) with small degrees of polymerization (DP2-DP4) were the major XOS hydrolyzate during SHPC degradation by rXyn162 and rXylCD2. In addition, rXyn162 and rXylCD2 could efficiently improve the hydrolysis of SHPC by commercial cellulase. The present study suggested the potential application of rXyn162 and rXylCD2 in the field of biomass pretreatment and biofuel production. Graphical abstract: Highlights: Novel endo-1, 4-xylanase and β-xylosidase were heterologously expressed and characterized. Synergistic hydrolysis of xylan and SHPC by rXyn162 and rXylCD2 was observed. XOS with small degrees of polymerization were majorly present in SHPC hydrolysate. rXyn162 and rXylCD2 enhanced SHPC hydrolysis by commercial cellulase.